The roles of NADPH oxidase in modulating neutrophil effector responses - Zeng, Melody Y. (Mol Oral Microbiol, 2019)
Neutrophils are phagocytic innate immune cells essential for killing bacteria via activation of a wide variety of effector responses and generation of large amounts of reactive oxygen species (ROS). Majority of the ROS in neutrophils is generated by activation of the superoxide-generating enzyme nicotinamide adenine dinucleotide phosphate (NADPH) oxidase. Independent of their anti-microbial function, NADPH oxidase-derived ROS have emerged as key regulators of host immune responses and neutrophilic inflammation. Data from patients with inherited defects in the NADPH oxidase subunit alleles that ablate its enzyme function as well as mouse models demonstrate profound dysregulation of host inflammatory responses, neutrophil hyperactivation and tissue damage in response to microbial ligands or tissue trauma. A large body of literature now demonstrates how oxidants function as essential signaling molecules that are essential for the regulation of neutrophil responses during priming, degranulation, neutrophil extracellular trap formation, and apoptosis, independent of their role in microbial killing. In this review we summarize how NADPH oxidase-derived oxidants modulate neutrophil function in a cell intrinsic manner and regulate host inflammatory responses. In addition, we summarize studies that have elucidated possible roles of oxidants in neutrophilic responses within the oral mucosa and periodontal disease.